I do not like stories - Larsen, Andrew, 1960- (Owlkids Books, 2020)
"The story itself is simple. Boy gets up, boy goes to school, boy comes home from school, boy goes to bed. Boy seems a bit grumpy, until the end of the day when he comes home to his cat, who he clearly loves. The boy's story is told in a traditional picture book style--in the meantime, the cat's story is told in graphic panels. Throughout the entire book, the boy tells the reader how much he dislikes stories, all kinds of stories inspired by his surroundings and whatever he is doing - so, he doesn't like stories about getting up in the morning, or stories about planes or trains or busses or bikes, or about boring old buildings (illustration shows his school), or stories about going home at the end of the day... And while the boy is going through his day, the cat sets off searching for the boy, following what she thinks is the school bus, only to be mistaken again and again by other things that are also bright yellow: An ice cream stand, a fire hydrant, a taxi, a public mailbox (these yellow objects are a bright color pop on each page, leading the cat and the story forward). Meanwhile the boy is at school, and the only time he looks happy and engaged is when he is shown drawing a picture of his cat. The cat, still wandering about the town, sees the boy in the bus heading home, and rushes to greet him, already back inside by the time the boy opens the door. At this point, the story changes - he's happy to be home and with his cat. He plays with her, feeds her, and snuggles into bed with her. In the end, the reader will understand that the boy doesn't really dislike stories -- it just needs to be the right story!"--